Validation of the prescription drug monitoring program Web site - Hozack, MD, Bryan A.; Rivlin, MD, Michael; Graham, BS, Jack; Lutsky, MD, Kevin F.; Beredjiklian, MD, Pedro K. (Journal of Opioid Management, 2019)
Objective: Evaluate the accuracy of the Pennsylvania Prescription Drug Monitoring Program (PA PDMP) in patients undergoing upper extremity procedures. The authors hypothesized that the PA PDMP would provide an accurate account of the prescriptions that were filled. Design: The authors prospectively collected post-operative pain prescription information of patients undergoing outpatient upper extremity surgery over a 2-week period. Patient-reported prescription-filling of opioid was cross-referenced with the PA PDMP information. Setting: The study was performed at one private institution. Patients: One hundred and thirty-nine consecutive patients undergoing upper extremity procedures. Main outcome measure(s): The PA PDMP information was cross-referenced with the post-operative prescription in the medical record to confirm the patient filled the surgeon’s prescription. Results: Of the 111 patients who reported filling their prescription, 107 (96.4 percent) of these were confirmed on the PA PDMP Web site (96.4 percent sensitivity; 95% confidence interval [CI]: 91.0-99.0 percent). None of 28 patients who did not fill their prescription appeared in the database search, resulting in 100 percent specificity (95% CI: 87.7-100 percent). Consequently, the overall accuracy of the PA PDMP was shown to be 97.1 percent (95% CI: 92.8-99.2 percent). Conclusions: The authors’ results suggest that the PA PDMP and its many supplementary databases are accurate as it relates to monitoring opioid prescriptions.